RETRACTED: Open Resection Compared to Mini-Invasive in Colorectal Cancer and Liver Metastases: A Meta-Analysis - Gong, Jie; Gao, Fengwei; Xie, Qingyun; Zhao, Xin; Lei, Zehua (Frontiers in Surgery, 2021)
Background We performed a meta-analysis to evaluate the outcomes of minimally invasive surgery and open surgery in the simultaneous resection of colorectal cancer and synchronous colorectal liver metastases. Methods A systematic literature search up to April 2021 was done and 13 studies included 1181 subjects with colorectal cancer and synchronous colorectal liver metastases at the start of the study; 425 of them were using minimally invasive surgery and 756 were open surgery. They were reporting relationships between the outcomes of minimally invasive surgery and open surgery in the simultaneous resection of colorectal cancer and synchronous colorectal liver metastases. We calculated the odds ratio (OR) or the mean difference (MD) with 95% confidence intervals (CIs) to assess the outcomes of minimally invasive surgery and open surgery in the simultaneous resection of colorectal cancer and synchronous colorectal liver metastases using the dichotomous or continuous method with a random or fixed-effect model. Results Minimally invasive surgery in subjects with colorectal cancer and synchronous colorectal liver metastases was significantly related to longer operation time (MD, 35.61; 95% CI, 7.36-63.87, p=0. 01), less blood loss (MD, -151.62; 95% CI, -228.84- -74.40, p<0.001), less blood transfusion needs (OR, 0.61; 95% CI, 0.42-0.89, p=0.01), shorter length of hospital stay (MD, -3.26; 95% CI, -3.67- -2.86, p<0.001), lower overall complications (OR, 0.59; 95% CI, 0.45- 79, p<0.001), higher overall survival (OR, 1.66; 95% CI, 1.21-2.29, p=0.002), and higher disease-free survival (OR, 1.49; 95% CI, 1.13-1.97, p=0.005) compared to open surgery. Conclusions Minimally invasive surgery in subjects with colorectal cancer and synchronous colorectal liver metastases may have less blood loss, less blood transfusion needs, shorter length of hospital stay, lower overall complications, higher overall survival, and higher disease-free survival with longer operation time compared to open surgery. Furthers studies are required to validate these findings.